ANALISIS TERHADAP BRAND PREDICTABILITY, BRAND LIKING, BRAND COMPETENCE, BRAND REPUTATION, DAN TRUST IN THE COMPANY YANG MEMPENGARUHI LOYALITAS MEREK KONSUMEN SEPATU FUTSAL NIKE DI KOTA YOGYAKARTA - , Galih Kus Andhika ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to study empirically the influence of brand predictability, brand liking, brand competence, brand reputation, and trust in the company on brand loyalty. Brands studied were NIKE futsal shoes. Respondents of this study is user NIKE futsal shoes in the city of Yogyakarta. The analytical tools used to answer the purposes of this study is Multiple Linear Regression. 250 customers NIKE futsal shoes in the city of Yogyakarta taken as samples, and the results showed that the brand predictability and trust in the company influence on brand loyalty. An interesting finding is that no influence of brand liking, brand competence and brand reputation in brand loyalty NIKE futsal shoes in the city of Yogyakarta.